Meeting the Leadership Challenge of Employee Well-Being Through Relationship PsyCap and Health PsyCap. (February 2013) - Luthans, Fred; Youssef, Carolyn M.; Sweetman, David S.; Harms, Peter D.
Increasing recognition is being given to the role that employee overall well-being plays in desired outcomes of today's organizations. To help organizational leaders searching for understanding and answers, we propose that the positive core construct of psychological capital (or simply PsyCap), consisting of the positive psychological resources of hope, efficacy, resiliency, and optimism can be extended into the well-being domain. Although PsyCap has been clearly demonstrated to be related to employee attitudes, behaviors, and performance, linking it with other life domains relevant to overall well-being has yet to be tested. After first building a comprehensive conceptual foundation for extending PsyCap into the well-being domain, we empirically found that a cross section of employees' ( N = 523) "Relationship PsyCap" and "Health PsyCap" were related to both their respective satisfaction appraisals and desired objective outcomes. In addition, these two extended life satisfactions, along with the already well-established work satisfaction, combined to relate to the appraisal of the study participants' overall well-being. This well-being was in turn found to be related to their overall level of PsyCap. These findings have implications for helping leaders meet the challenges they face in both understanding and helping develop the overall well-being of their employees.